A relação entre jovens e o MST no assentamento 1º de Janeiro, Palmeiras do Tocantins. - Chaves, Ana Cláudia Alves (Universidade Federal do Tocantins, 2021)
The January 1 settlement is a conquest of the people with the organization and planning of the landless rural workers movement, which in turn has a large number of young people living there, and with a view to understanding the relationship of these young people with the MST, which was the main organ in the dispute for the land and in the conquest of the settlement, that I decided to choose this theme for this monograph, was not very easy, because in the case of young people, each one has its peculiarities and totally different customs. makes it difficult for us to make accurate data analysis. Another factor very relevant to this research was the issue of MST beginning to be more frequent in the settlement, thus drawing the attention of young children and older to the movement. There is a very important milestone in the conquest for the land, because in January of this year (2018), the settlement became 20 years old, making it the oldest settlement conquered by the land reform struggle in Tocantins led by the MST. Ten young people and adults were interviewed for this research, two of them from the MST, with the objective of understanding how the MST is treated in relation to the youth of the settlement, observing and analyzing the integration of these young people with militancy, consideration some important aspects to better understand each opinion, aspects such as the particular culture of each individual, wanted are their priorities in regards to sports, leisure, work and so also their perspective on studies and future academic. The results were satisfactory, regarding the hypothesis raised, and that with the rigor of the parents, the frequency of MST and the interventions of the church, the perspective of these young people is changing, nevertheless, a deeper research should be done in future researches, and even even some interventions, with projects of support to these young people, so that they can heal any frequent doubts, in the course of this work will be understood better this question.